ANALIYSIS OF SEXUAL RISKY FACTORS FOR ADOLESCENTS IN THE KOTO TINGGI HEALTH CENTER IN LIMA PULUH KOTA 2020 - Rosmi Eni (LLDIKTI Wilayah X, 2021)
Risk sexual behavior will increase the chance of someone who does it bring unwanted consequences such as pregnancy outside marriage / unwanted pregnancy, acts of abortion, dropping out of school, psychosocial disorders, sexually transmitted diseases and being infected with HIV / AIDS. The purpose of this study is to determine the factors associated with risky sexual behavior in adolescents in the working area of the Koto Tinggi Health Center in Lima Puluh Kota 2019,The method used is a quantitative research method of analytic study using a cross sectional approach, the sampling technique using proportional stratified random sampling of 196 respondents. Data collection tool uses a questionnaire. Data analysis used chi square test and multiple logistic regression. The result of the statistical test shows that there is a relationship between age, knowledge, the role of peers, access to information, family roles, lifestyle, religious understanding of risky sexual behavior, and there is no relationship between the role of school and sex on risky sexual behavior of adolescents in the work area Koto Tinggi Health Center in Lima Puluh Kota 2019. The results showed that the most dominant factor influencing risky sexual behavior was access to information. It is expected that the Ministry of Health, schools and the BKKBN can implement the Youth Care Health Services Program optimally. Mental Health Nursing Program implementation of generalist and specialist therapy